Accuracy of CBCT, Digital Radiography and Cross-Sectioning for the Evaluation of Mandibular Incisor Root Canals - Assadian, Hadi; Dabbaghi, Arash; Gooran, Morteza; Eftekhar, Behrouz; Sharifi, Sanaz; Shams, Nassim; Dehghani Najvani, Ali; Tabesh, Hamed (Iranian Endodontic Journal, 2016)
ntroduction: The aim of this study was to compare the accuracy of cone-beam computed tomography (CBCT), digital radiography and tooth sectioning in evaluating root canal morphology of mandibular incisors in an in vitro setting. Methods and Materials: A total of 76 samples were imaged using CBCT, and digital radiography in straight and angled views. The samples were then sectioned at different distances from the apex for further visualization under stereomicroscope. The agreement between the observers was statistically analyzed by kappa correlation coefficient and the chi-square test. Results: The results showed that the majority of the samples had a single canal (Vertucci’s Type I). CBCT analysis reported more frequent multi-canal roots in comparison with the other techniques. In pairwise comparisons, the highest agreement was found between digital radiographic imaging and microscopic cross-sectioning both in terms of canal configuration and the number of root canals. Conclusion: None of the used imaging techniques per se could adequately show the exact internal anatomical configuration in accordance with the gold standard. Keywords: Anatomy; Cone-Beam Computed Tomography; Digital Radiography; Incisor Teeth